Heartless ebook A paranormal romance. - Showalter, Gena (Immortal Enemies, 2021)
Don't miss the first book in New York Times bestselling author Gena Showalter's sexy, heart-pounding new Immortal Enemies series about a ruthless warrior hellbent on revenge, the fae princess determined to thwart him at every turn, and the desire that threatens to consume them in Heartless. "One of the premier authors of paranormal romance. Gena Showalter delivers an utterly spellbinding story!" —Kresley Cole, #1 New York Times bestselling author Vengeance is irresistible... Kaysar the Unhinged One, fae King of Midnight, can drive anyone to madness with his song. A ruthless warrior forged in hate, he lives to force his enemies to their knees. He will stop at nothing to succeed—even abducting and seducing his foe's beloved bride to ensure his own child one day sits on the male's throne. Except, his prize escapes to the mortal realm before the first kiss, her heart transplanted into a human beauty with dangerous secrets... Chantel "Cookie" Bardot is a professional gamer girl great at trash-talking, bad at peopling. After a long-awaited surgery, she begins to morph into a powerful fae princess. Catapulted into a strange land ruled by a cruel but seductive villain, she must battle flesh-and-blood monsters and navigate royal intrigues. But the true danger is Kaysar, whose every wicked touch tempts her beyond reason. Should she run...or descend into the darkness with him? Don't miss Ruthless, the second book in New York Times bestselling author Gena Showalter's captivating and unforgettable Immortal Enemies series.